Identifying The Need For Counseling Support For Hearing Siblings Of Deaf Individuals: Evidence From A Case Study - Aisha Nadya; Achmad Ali Syaifudin; Karel Yulius Jimmy Tuerah (Ma'soem University, 2025)
This study addresses the limited attention given to hearing siblings of individuals with deafness, a group that often remains overlooked within family support structures despite their critical roles. These siblings frequently experience emotional and social challenges as a result of the disproportionate focus placed on the needs of their deaf sibling, potentially impacting their well-being. This research aims to explore the lived experiences of hearing siblings and identify their specific needs for guidance and counseling support. Using a qualitative case study approach, the study involved four participants selected through purposive sampling, all of whom were actively engaged in their deaf sibling’s daily life. Data were collected through semi-structured interviews and analyzed using a thematic analysis approach. The analytical stages included verbatim transcription, open coding, theme categorization, and validation through member checking. The findings revealed five major themes: emotional burden, social challenges, diminished well-being, the urgent need for support, and perception of counseling. Participants described increased responsibility, feelings of neglect, stigma, and social isolation, all contributing to low self-esteem and psychological stress. Importantly, counseling was perceived positively as a “safe space,” but participants emphasized the need for counselors who are knowledgeable about deafness and sibling dynamics. The study recommends the development of tailored guidance and counseling programs that address the specific emotional, educational, and interpersonal needs of hearing siblings of deaf individuals. Additionally, it calls for greater public awareness and further longitudinal research to inform sustainable and inclusive support systems.